If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -6y = -5 Solving -1x + -6y = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. -1x + -6y + 6y = -5 + 6y Combine like terms: -6y + 6y = 0 -1x + 0 = -5 + 6y -1x = -5 + 6y Divide each side by '-1'. x = 5 + -6y Simplifying x = 5 + -6y
| 21/5+x=6 | | 4(x-80)+10=-10 | | 4(5x+6)+7(12-x)= | | 3+z=-19 | | -1+a=0.5 | | 69-(7x+4)=7(x+5)+x | | [-x]=-1 | | 9x-18=40+3x | | 7-12x/4 | | 2x+3x+9=8 | | 6x^2+28x+26=0 | | 10=-12-e | | (7x+13)+(7x-2)= | | -2(y-3)=y+4s | | 20x=-80 | | -6y^2=-54 | | [-4g+2]=8 | | -4(6r-7)=35 | | (54x+65y)+(-11x+45y)= | | 4x+44=-19+x | | 3(x+5)=2(2x+11) | | (2x-5)(x-7)=0 | | 6(4w+8)=8 | | 10x+10=-40 | | X-9(3-x)=5+10x | | -7(2t+10)=-42 | | 8(2-p)=27 | | 3(f-9)=-30 | | (14x+6y)+(48x+34y)= | | 6+55x=44x+9 | | 8w+4x=5w-6x | | -4a+7=-17 |